Voices of Future English Teachers: A Narrative Inquiry of Preservice Teachers' Experiences and Perceptions of World Englishes - Buton, Nurdayanti; Ibrahim, Ibrahim; Hamid, Ade Ismail Ramadhan (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
This study examines how pre-service English teachers' life experiences, beliefs, and identity conflicts influence their perceptions and understandings of World Englishes (WE). Using a qualitative method with a narrative inquiry approach, this study used interviews and reflective journals from four sixth-semester students of an English education program at one of the religiously based private universities in East Kalimantan. The findings were that WE understanding developed through exposure to media and personal experiences, as well as language skills courses. These pre-service English teachers perceived that WE is important for students and has a positive impact on students' language skills. Despite challenges, the pre-service English teachers were committed to creating an inclusive learning environment and valued the diversity of the English language. This research suggests further exploration of how World Englishes influence teachers' teaching practices.